Compulsory Purchase and Compensation - Denyer-Green, Barry (EG Books, 2005)
This is the eighth edition of an established book widely used by students and practitioners of estate management, surveying, valuation, planning and law. It has been extensively revised to reflect the relevant provisions of the Planning and Compulsory Purchase Act 2004 and other recent legal developments.